Australian Institute of Sport and the Australian Paralympic Committee position statement: urinary tract infection in spinal cord injured athletes. Issue 19 (13th April 2015) - Compton, Stacey; Trease, Larissa; Cunningham, Corey; Hughes, David
Abstract : Patients with spinal cord injuries are at increased risk of developing symptomatic urinary tract infections. Current evidence-based knowledge regarding prevention and treatment of urinary tract infection in the spinal cord injured population is limited. There are currently no urinary tract infection prevention and management guidelines specifically targeted towards elite spinal cord injured athletes. This position statement represents a set of recommendations intended to provide clinical guidelines for sport and exercise medicine physicians and other healthcare providers for the prevention and treatment of urinary tract infection in spinal cord injured athletes. It has been endorsed by the Australian Institute of Sport (AIS) and the Australian Paralympic Committee (APC).